Cerebral amyloid angiopathy‐related inflammation and dementia. Issue 2 (10th March 2021) - Sakai, Kenji; Yamada, Masahito
Abstract: Cerebral amyloid angiopathy (CAA) is a disorder characterized by deposition of amyloid on the leptomeningeal and cortical blood vessels. Sporadic amyloid β (Aβ)‐type CAA is the most common type of CAA. Although CAA is well known as a cause of recurrent cerebral lobar hemorrhage, inflammation and vasculitis (CAA‐related inflammation [CAA‐ri]) induced by deposited Aβ on the vessel walls is emerging as a treatable condition. Furthermore, dementia could develop regardless of the presence of Alzheimer's disease pathology. The estimated total number and prevalence of CAA‐ri in Japan was reported as follows: 170 and 0.13 per 100 000 population, respectively. The estimated total number of CAA‐related intracerebral hemorrhage was 5900. The crude prevalence rate of CAA‐related intracerebral hemorrhage was 4.64 per 100 000 population. The patients with CAA‐ri show acute or subacute‐onset cognitive impairment, behavioral changes and headache. Brain magnetic resonance imaging is a useful tool for the diagnosis of CAA‐ri, showing asymmetrical white matter abnormalities and occasional meningeal enhancement. Furthermore, elevation of anti‐Aβ antibodies and inflammatory markers in the cerebrospinal fluid would be useful for clinical diagnosis. Clinical diagnostic criteria were proposed; however, neuropathological examination obtained by brain biopsy is still warranted to confirm severe Aβ deposition and vasculopathic changes with lymphocytic infiltrations and/or granulomatous vasculitis. No validated protocol of treatment has been established. Nearly 80% of the patients with CAA‐ri improved after immunosuppressant therapy, including corticosteroid and cyclophosphamide. Early treatment is necessary to prevent the development of irreversible sequela in the brain. Abstract : Cerebral amyloid angiopathy (CAA) is a disorder characterized by deposition of amyloid on the leptomeningeal and cortical blood vessels. Inflammation and vasculitis (CAA‐related inflammation: CAA‐ri) induced by deposited Aβ on the vessel walls is emerging as a treatable condition.